The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12032-015-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression classifier for the diagnosis of indeterminate thyroid nodules: a meta-analysis

Abstract: Prior studies demonstrate that a novel genomic test, the gene expression classifier (GEC), could identify a benign gene expression signature in those nodules with indeterminate cytology with a negative predictive value of greater than 95 %. Examine the performance of the AFIRMA gene expression classifier in predicting benign and malignant nodules in patients with cytologically indeterminate nodules. MEDLINE and EMBASE search for studies meeting eligibility criteria between January 1, 2005, and August 30, 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Afirma, a proprietary gene-expression classifier with a high negative predictive value, is designed to identify benign nodules among those with inconclusive results on cytopathological testing. 24,25 Alternatively, next-generation sequencing of a panel of oncogenes and tumor-suppressor genes identifies nodules with mutations that have been associated with thyroid cancer, with high positive and negative predictive values. 26 These two tests appear to reduce the incidence of unnecessary surgery, although their reliability in various clinical-practice settings remains to be established.…”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…Afirma, a proprietary gene-expression classifier with a high negative predictive value, is designed to identify benign nodules among those with inconclusive results on cytopathological testing. 24,25 Alternatively, next-generation sequencing of a panel of oncogenes and tumor-suppressor genes identifies nodules with mutations that have been associated with thyroid cancer, with high positive and negative predictive values. 26 These two tests appear to reduce the incidence of unnecessary surgery, although their reliability in various clinical-practice settings remains to be established.…”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…Based on the initial validation studies, Afirma Thyroid FNA Analysis (GEC/GSC) garners strength by targeting genetic signatures and mRNA expression to exclude malignancy . Its high NPV and low PPV were promoted to foster its use as a rule‐out test . Since its release as a novel testing platform, several authors have investigated the utility of Afirma GEC and its performance in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Its high NPV and low PPV were promoted to foster its use as a rule‐out test . Since its release as a novel testing platform, several authors have investigated the utility of Afirma GEC and its performance in clinical practice . Single institutional studies and large meta‐analyses of data demonstrated a compelling reduction in the number of unnecessary surgical operations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designed to lower patient morbidity and the cost of care by decreasing unnecessary surgery for benign thyroid nodules, the majority of studies have demonstrated the utility of the Afirma GEC, whereas others have questioned the actual cost‐benefit analysis of reflexively incorporating it into clinical care . Behind some of the various interpretations of the performance of the GEC are the inherent differences in agreement among thyroid cytopathologists .…”
Section: The Development Of Thyroid Molecular Testingmentioning
confidence: 99%